The Effectiveness of Islamic Financial Intermediation Compared to Ribaoui Financial Intermediation - HAMDOUNI, Amina; KHALDI, Khadidja (Journal of Posthumanism, 2025)
The financing systems in modern economies are primarily divided into two broad categories: Islamic financing, based on principles of profit and loss sharing, and conventional Riba-based (classical) financing, which relies on fixed income contracts. While Islamic financing emphasizes ethical considerations and risk-sharing, conventional financing typically provides fixed returns to lenders. The purpose of this study is to compare these two financing systems in terms of their economic efficiency, specifically focusing on the returns offered to investors.This study employs mathematical analysis using the principles of partial equilibrium theory, particularly for risk-averse investors. The two financing models—Islamic financing based on variable yields tied to the realized profits of a project and subject to zakat if applicable, and the Riba-based financing system with fixed income contracts—are analyzed through these frameworks. The comparison focuses on investor returns and risk-sharing dynamics, without involving animal models or preregistration numbers, as this is a theoretical economic study. The study finds that, for risk-averse investors, financing contracts based on profit and loss sharing (as in the Islamic system) yield higher returns compared to fixed income contracts common in the Riba-based (classical) financing system. The analysis shows that the risk-sharing nature of Islamic financing allows for more favorable returns in certain market conditions. The findings suggest that Islamic financing systems, with their emphasis on profit and loss sharing, offer higher returns for risk-averse investors when compared to conventional Riba-based financing. These results provide support for the economic efficiency and attractiveness of profit-sharing contracts over fixed-income models in specific investment scenarios.